Towards a Definition of Experience. - Clough, Barbara A. (The Accounting Review, 1973)
The article cites the value and specific guidelines of practical work experience that the Certified General Accountants' Association of Canada considered before certification into the accounting profession is granted. One of the main problems encountered in reviewing various professional assessments of the Experience Requirement has been in understanding what different groups mean by the word "experience." None of the various associations surveyed seems to define what they are talking about and therefore they seem to be using the word "experience" to mean a variety of things. There is a discrepancy among Associations and academics as to what experience really is. The Association should try to provide the student with the tools necessary to acquire each level of competency, but this author feels that it is only at the third level of competency that the Association can try to provide specific guidelines. The increasing pressures and continual changes of everyday social and business life will confront our students when they start their first job. Three levels of experience are necessary to produce an effective accountant, they are: Accounting experience, General business experience and Broad life experience. The Association should define and provide for each of these levels of experience, but perhaps can specifically define and lay guidelines only for the Accounting Experience necessary before certification.